Modeling the Community-Based Development Approach in Neighborhood Development Planning with Structural Equation Methods (Case Study: Golkaran Neighborhood of Abarkouh City) - hasan kabouri; seyed ali almodaresi; mohammad hossin ramesht; mohammad mehdi karim nejad; malihe zakerian (تحقیقات کاربردی علوم جغرافیایی)
The aim of the present study was to model a community-  based development approach in neighborhood development planning using structural equation methods. The analytical-descriptive research method is applied with a practical purpose and the approach governing the research space with a methodological focus is a quantitative approach. Two library and survey methods have been used to gather information on the subject of study. The statistical population studied in this study is all people over 18 years of age in the study neighborhood of Abarkouh city (Golkaran). Using a questionnaire tool that was adjusted according to the Likert spectrum, it was collected and its reliability was determined by Cronbach's alpha coefficient, which includes both the total coefficient and the coefficient of different sections in the dimensions of the questionnaire and also to determine the validity of the questionnaire. Experts in the field of urban planning benefited. In the data analysis section, two levels of descriptive statistics, mean and standard deviation and inferential statistics were used to measure and evaluate the amount of components affecting the community-based development approach and also to formulate an operational model in the study neighborhood using structural equation model in Amos software environment. Was. This model examines the interrelationships and interactions of variables and the degree of effectiveness and effectiveness of each other.The results of data analysis using the model of structural equations show that having a community-based approach to neighborhood development has a direct and significant effect on promoting neighborhood development.